Blunt cerebrovascular injuries: Outcomes from the American Association for the Surgery of Trauma PROspective Observational Vascular Injury Treatment (PROOVIT) multicenter registry. Issue 6 (June 2021) - Russo, Rachel M.; Davidson, Anders J.; Alam, Hasan B.; DuBose, Joseph J.; Galante, Joseph M.; Fabian, Timothy C.; Savage, Stephanie; Holcomb, John B.; Scalea, Thomas M.; Rasmussen, Todd E.
Abstract : BACKGROUND: Administering antithrombotics (AT) to the multiply injured patient with blunt cerebrovascular injury (BCVI) requires a thoughtful assessment of the risk of stroke and death associated with nontreatment. Large, multicenter analysis of outcomes stratified by injury grade and vessel injured is needed to inform future recommendations. METHODS: Nine hundred and seventy-one BCVIs were identified from the PROspective Vascular Injury Treatment registry in this retrospective analysis. Using multivariate analysis, we identified predictors of BCVI-related stroke and death. We then stratified these risks by injury grade and vessel injured. We compared the risk of adverse outcomes in the nontreatment group with those treated with antiplatelet agents and/or anticoagulants. RESULTS: Stroke was identified in 7% of cases. Overall mortality was 12%. Both increased with increasing BCVI grade. Treatment with ATs was associated with lower mortality and was not significantly affected by the choice of agent. Withholding ATs was associated with an increased risk of stroke and/or death across all subgroups (Grade I/II: odds ratio [OR], 4.66; 95% confidence interval [CI], 2.48–8.75; Grade III: OR, 7.0; 95% CI, 2.01–24.5; Grade IV: OR, 4.43; 95% CI, 1.76–11.1) even after controlling for covariates. Predictors of death included more severe trauma, Grade IV injury, and the occurrence of stroke. Arterial occlusion, hypotension, and endovascular intervention were significant predictors of stroke. Patients that experienced a BCVI-related stroke were at a 4.2× increased risk of death. The data set lacked the granularity necessary to evaluate AT timing or dosing regimen, which limited further analysis of stroke prevention strategies. CONCLUSION: Stroke and death remain significant risks for all BCVI grades regardless of the vessel injured. Antithrombotics represent the only management strategy that is consistently associated with a lower incidence of stroke and death in all BCVI categories. In the multi-injured BCVI patient with a high risk of bleeding on anticoagulation, antiplatelet agents are an efficacious alternative. Given the 40% mortality rate in patients who survived their initial trauma and developed a BCVI-related stroke, nontreatment may no longer be a viable option. LEVEL OF EVIDENCE: Epidemiological III; Therapeutic IV. Abstract : Supplemental digital content is available in the text.